A Novel Distributed Privacy Paradigm for Visual Sensor Networks Based on Sharing Dynamical Systems. (15th October 2006) - Luh Luh, William William; Kundur Kundur, Deepa Deepa; Zourntos Zourntos, Takis Takis
Abstract : Visual sensor networks (VSNs) provide surveillance images/video which must be protected from eavesdropping and tampering en route to the base station. In the spirit of sensor networks, we propose a novel paradigm for securing privacy and confidentiality in a distributed manner. Our paradigm is based on the control of dynamical systems, which we show is well suited for VSNs due to its low complexity in terms of processing and communication, while achieving robustness to both unintentional noise and intentional attacks as long as a small subset of nodes are affected. We also present a low complexity algorithm called TANGRAM to demonstrate the feasibility of applying our novel paradigm to VSNs. We present and discuss simulation results of TANGRAM.